2013
DOI: 10.1016/j.rmed.2013.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Harms of unintentional leaks during volume targeted pressure support ventilation

Abstract: Most of the studied ventilators with a single-limb circuit with intentional leak correctly estimate the expiratory VT and therefore successfully maintain the preset minimal VT during unintentional leaks, in contrast to most of the studied ventilators with a double-circuit, which paradoxically are not able to directly measure expiratory VT. Importantly, the VT-PSV mode, when used with most ventilators with expiratory valve or double-circuit, can paradoxically exacerbate the VT drop during unintentional leaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 20 publications
1
28
1
1
Order By: Relevance
“…Nevertheless, in a study collecting data from 209 individuals with NMD, 82 (39%) patients were using the pressure-controlled mode, while 122 (59%) were on a volume-controlled mode [46]. Although pressure-controlled modes better compensate with nonintentional leaks [41], the best results have been found when pressure-controlled modes are coupled with a bilevel ventilator in vented configuration [27, 28, 47, 48]. …”
Section: Modes and Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, in a study collecting data from 209 individuals with NMD, 82 (39%) patients were using the pressure-controlled mode, while 122 (59%) were on a volume-controlled mode [46]. Although pressure-controlled modes better compensate with nonintentional leaks [41], the best results have been found when pressure-controlled modes are coupled with a bilevel ventilator in vented configuration [27, 28, 47, 48]. …”
Section: Modes and Monitoringmentioning
confidence: 99%
“…On the other hand, the nonvented circuit configuration undercompensated in order to maintain the preset VT [47, 48]. …”
Section: Modes and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…[158][159][160] In 2 recently published bench studies, the effect of unintentional leaks on target-volume ventilation was investigated under different conditions. In a study by Khirani et al, 161 single-limb circuits with intentional leaks estimated the expiratory target volume more accurately compared with single circuits with an expiratory valve or ventilators using a double circuit. Additionally, Carlucci et al 162 reported that vented circuits are able to better compensate for leaks compared with nonvented circuits with an active valve.…”
Section: Niv Modes: Recent and Future Developmentsmentioning
confidence: 99%
“…In contrast, when the tidal volume is estimated by the expired volume, the tidal volume can be overestimated. 14,15 Finally, the majority of the PRVC ventilation devices are currently not reliable during unintentional leak, underlining the need to check these modes during unintentional leak.…”
Section: Evaluation Of the Patients' Equipment Versus The Prescribersmentioning
confidence: 99%